Synthesis and Characterization of Tannin Based Porous Cation Exchange Resins from Cassia auriculata (Ranawara) - Kuruppu, K.A.D.U.M.; Karunanayake, L. (Faculty of Applied Sciences, University of Sri Jayewardenepura, 2019)
Tannins are one of the most abundant compounds in the nature. Naturally tannins have ion exchanging capability. Conversely, tannins are highly water soluble compounds, thus natural tannins cannot be used as ion exchangers. In this study, tannins extracted from Cassia auriculata (Ranawara) were used to synthesise renewable tannin based porous cation exchange resin systems. Essentially, the applicability of these resin systems as an ion exchange resin were considered. Identification of the Tannin was carried out by using ferric chloride test, nitrous acid test and acid butanol tests. Total polyphenolic content of Cassia auriculata was 13.30% (w/w) and it was calculated by using Folin-ciocalteau method. Tannin-Formaldehyde resin was prepared, and the ion exchange capacity was measured. Then the Tannin-Formaldehyde resin was sulfonated to increase the ion exchange capacity by refluxing with concentrated H2SO4. Then, the ion exchange capacity of the resin was further increased by introducing a porous structure using virgin coconut oil as the porogenic agent. Ion exchange capacity, solubility, Fourier transform infrared spectroscopy and scanning electron microscopy analysis were used to characterise the resin systems. The modified resin with high fraction of surfactant contains mostly open porous structures and it has the highest IEC (0.9550 meq/g) among the synthesized resin systems.
Keywords: Cassia auriculata (Ranawara), porous tannin-formaldehyde cation exchange resin, ion exchange capacity, FTIR, SEM